Pengaruh Social Media Marketing Instagram, Kualitas Pelayanan Dan Brand Image Terhadap Keputusan Pembelian Pada Labricca.Id - Reza Adi Yudanto; Tuti Wediawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to examine the influence of Social Media Marketing Instagram, service quality, and brand image on purchasing decisions at Coffee Shop Labricca.Id in Samarinda. This research used a quantitative approach with a survey technique using a questionnaire distributed to 100 consumer respondents, both male and female, who have made purchases at Coffee Shop Labricca.Id more than once. The sampling technique used was purposive sampling based on the Slovin formula. The collected data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. The results of the analysis show that Instagram social media marketing, service quality, and brand image have a positive and significant influence on purchasing decisions at Coffee Shop Labricca.Id in Samarinda. These findings indicate that effective use of Instagram social media marketing, providing good service quality, and building a positive brand image can enhance consumer purchasing decisions at Coffee Shop Labricca.Id. The practical implication of these findings is that Coffee Shop Labricca.Id needs to pay attention to and improve their social media marketing strategies, service quality, and brand image to enhance consumer purchasing decisions.